Interstitial cells of Cajal in the human fetal small bowel as shown by c-kit immunohistochemistry. Issue 1 (1st January 1999) - Wester, T; Eriksson, L; Olsson, Y; Olsen, L
Abstract : Background: Interstitial cells of Cajal (ICCs) express the tyrosine kinase receptor c-kit, which is required for their development and spontaneous pacemaker activity in the bowel. From murine models it has been proposed that ICCs do not develop until after birth, but more recent findings indicate that c-kit is expressed early in the embryonic period. The temporal development of ICCs in the human gut remains unknown. Aim: To investigate ICCs in the human fetal small bowel using c-kit immunohistochemistry. Subjects: Small bowel specimens were obtained at post mortem examination of 16 fetuses and nine neonates, eight of whom were premature, born at gestational ages of 13 to 41 weeks, without gastrointestinal disorders. Methods: Immunohistochemical analysis was performed on material fixed in formalin and embedded in paraffin. The specimens were exposed to antibodies raised against c-kit (an ICC marker) and neurone specific enolase (a general neuronal marker). The ABC complex method was used to visualise binding of antibodies to the corresponding antigens. Results: c-kit immunoreactive cells were visualised from 13 weeks of gestation. The immunoreactivity was mainly localised in association with the myenteric plexus. From about 17–18 weeks of gestation, the ICCs formed a layer along the myenteric plexus, whereas this layer appeared to be disrupted at 13–16 weeks of gestation. Conclusions: ICCs are c-kit immunoreactive at least from a gestational age of 13 weeks in the human fetal small intestine. From 17–18 weeks of gestation until birth, they form a continuous layer around the myenteric ganglia.